Mimic security scheduling algorithm for industrial control under limited heterogeneous resource constraints - Ruyun ZHANG; Heyuan LI; Shunbin LI (Dianxin kexue)
Cyberspace mimic defense technology is an effective method to deal with backdoor attacks on unknown vulnerabilities in information systems.Its security is closely related to the number and the heterogeneity of the executors and the scheduling strategy.However, in the field of industrial control, the ecological resources of industrial application are relatively closed, and the number of realizable heterogeneous executors is limited.To solve the above problems, a mimic scheduling algorithm for industrial control under the constraints of limited heterogeneous resources was proposed.The experimental results show that the proposed algorithm for triple-redundancy mimic industrial control system was able to select a suitable executor to go online according to environmental characteristics adaptively.Even in a high-intensity attack environment, it can still maintain a high availability probability of 99.24%.